Competing loyalties in sports medicine: Threats to medical professionalism in elite, commercial sport. (April 2013) - Anderson, Lynley; Jackson, Steve
This paper explores the ways in which the environment of elite-level and, in particular, commercial sport produces expectations and pressures on sports doctors that may compromise their professional standards. Specifically, this paper addresses the pressures and demands that emerge from varying groups and individuals with whom doctors have relationships within the world of elite sport including: the athlete, coach, management, media (including broadcasters) and sponsors. Using grounded theory and drawing upon qualitative data collected from semi-structured interviews with 16 sports doctors the study explores the ethical concerns of medical practitioners working with elite athletes and teams in New Zealand. Key emerging themes include: the complex environment within which sports doctors work, including the limited control over their work environment, the pressures arising from the commercial interests of sport, the issue of competing obligations, and emerging threats to medical professionalism.